Detection of clonal immunoglobulin gene rearrangements in the peripheral blood progenitor cells of patients with multiple myeloma: the potential role of purging with CD34 positive selection. Issue 2 (April 1996) - Owen, R G; Haynes, A P; Evans, P A; Johnson, R J; Rawstron, A C; McQuaker, G; Smith, G M; Galvin, M C; Barnard, D L; Russell, N H; Child, J A; Morgan, G J
Abstract : Aims —To determine the extent of clonal cell contamination of peripheral blood progenitor cell (PBPC) collections in patients with multiple myeloma (MM) and to assess the purging efficacy of CD34 positive selection. Methods —PBPC collections from 29 patients with MM were analysed for the presence of clonal immunoglobulin heavy chain (IgH) gene rearrangements with a fluorescence based PCR technique. In addition, the PBPC from eight of the 29 patients were "purged" by selection of CD34 positive haematopoietic progenitors with an avidin-biotin immunoabsorption column (Ceprate). In each case the unmanipulated PBPC, CD34 positive and waste fractions were all assessed for the presence of clonal IgH rearrangements. Results —Clonal IgH rearrangements (identical with those demonstrated in diagnostic bone marrow samples) were demonstrated in 10 (35%) of 29 cases and seemed to be confined to those with significant residual bone marrow disease. Clonal rearrangements were evident in the PBPC of two of the eight patients who underwent CD34 selection; in both instances a "clonal purge" was seen as it was not possible to demonstrate the clonal rearrangement in the CD34 positive fraction. In four of the six remaining cases the normal polyclonal fingerprint could not be demonstrated in the CD34 positive fraction, which is consistent with a significant reduction in contaminating B cells. Conclusions —Clonal cells contaminate PBPC collections in a significant proportion of patients with MM and may be eliminated by CD34 positive selection.